Penentuan Konsentrasi Chemical Oxygen Demand (COD) Dalam Air Limbah Domestik Menggunakan Metode Spektrofotometri UV-Vis Berdasarkan Pada Pengaruh Waktu Refluks Dan Waktu Pengawetan - Muhaimin Muhaimin; Renaldy Ajie Prayoga; Endah Eniati (Stannum : Jurnal Sains dan Terapan Kimia, 2022)
The purpose of determining Chemical Oxygen Demand (COD) in samples of domestic wastewater is to determine the effect of variations in the reflux process time which is set to 0, 30, 60, 90, and 120 minutes as well as with variations in the testing time which are set to 0, 3, and 7 days. Determination of LOD and LOQ using a UV-Vis Spectrophotometer was also carried out and the regression equation y = 0.0003x + 0.0066 with a coefficient of determination (R2) was 0.998 with LOD and LOQ values ​​respectively 40.0416 mg O2/L and 133.4721 mg O2/L. Determination of the effect of reflux time and preservation time on COD levels was carried out statistically, namely the normality test (Kolmogorov-Smirnov Test) and homogeneity test (Levene Test) ending with a two-way ANOVA test with a probability or significance value of the inlet and outlet samples of 0.000 < 0.05 ( ). Reflux time affects COD levels, the longer the reflux time, the higher and more stable COD levels. Preservation time affects the decrease in COD levels, which is the longer the preservation time, the greater the decrease in COD levels.